Ocena poprawności stosowania zasad dobrych praktyk rolniczych w gospodarstwach agroturystycznych - Krzyżanowska, Krystyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2006)
In this article an attempt of assessing the correctness of using good agriculture practice in studied agroturism farms was made. Problems of organization of vegetable production, methods of raising soil fertility and organization of animal production were brought closer. Additionally, links between agriculture production and agroturism in studied farms was showed